Locally adaptive k parameter selection for nearest neighbor classifier: one nearest cluster - Bulut, Faruk; Amasyali, Mehmet Fatih (SPRINGER, 2017)
The k nearest neighbors (k-NN) classification technique has a worldly wide fame due to its simplicity, effectiveness, and robustness. As a lazy learner, k-NN is a versatile algorithm and is used in many fields. In this classifier, the k parameter is generally chosen by the user, and the optimal k value is found by experiments. The chosen constant k value is used during the whole classification phase. The same k value used for each test sample can decrease the overall prediction performance. The optimal k value for each test sample should vary from others in order to have more accurate predictions. In this study, a dynamic k value selection method for each instance is proposed. This improved classification method employs a simple clustering procedure. In the experiments, more accurate results are found. The reasons of success have also been understood and presented.
Keywords: Dynamic k parameter; k-NN; Classification; Clustering; Meta-parameter selection; CHOICE; Computer Science